Leaf structure and histochemistry of Ecballium elaterium (L.) A. Rich. (squirting cucumber) - Christodoulakis, N.S.; Kollia, K.; Fasseas, C. (Flora: Morphology, Distribution, Functional Ecology of Plants, 2011)
Light, scanning and transmission electron microscopy as well as histochemical reactions were employed to study the leaf structure and secretory activity of Ecballium elaterium, a hairy pharmaceutical perennial common in the Mediterranean region. The amphistomatic leaf has a peculiar structure due to special cells supporting the conductive bundles, a remarkable shortage of mechanical tissue, and the existence of pectin strands between mesophyll cells. The secreting activity is limited mostly to secretary hairs. These attributes of the Ecballium leaf fine structures do not resemble the common structure of leaves from Mediterranean plants and point to a peculiar strategy of this species coping with stress conditions of its habitat. © 2010 Elsevier GmbH.
Keywords: anatomy; cell organelle; Cucumis sativus; developmental biology; dicotyledon; Ecballium; Ecballium elaterium; electron microscopy; habitat type; Histochemistry; Leaf anatomy; leaf morphology; perennial plant; secondary metabolite; Secondary metabolites; Secreting hairs; Secretory structures